Determinants of Foreign Direct Investment in Indonesia Using Autoregressive Distributed Lag Modeling - Wulandari, Mutia Indah; Anam, Moh Saiful; Hadi Wijoyo, Handoko Sosro (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2025)
This study aims to analyse the influence of trade openness, institutional quality, and the exchange rate on Foreign Direct Investment (FDI) in Indonesia. The approach used is an ARDL regression analysis of time-series data from 2003 to 2023. The study's findings reveal that, in the short term, only trade openness has a significant positive effect on FDI. In contrast, in the long term, none of the other variables is substantial. These results highlight the importance of strengthening institutional improvements and maintaining trade policy stability to increase FDI attraction over the longer term.